Насіннєва продуктивність рослин Darmera peltata (Torr. ex Benth.) Voss (Saxifragaceae) в умовах міста Києва - Швець, Ірина; Колесніченко, Олена; Shvets, Iryna; Kolesnichenko, Elena (Східноєвропейський національний університет імені Лесі Українки, 2016)
Наведено результати дослідження особливостей насіннєвої продуктивності рослин Darmera peltata (Torr. ex Benth.) Voss у природних умовах м. Києва. Вивчено біологію цвітіння рослин D. peltata на території колекційної ділянки Ботанічного саду НУБіП України. Здійснено оцінку потенційної й фактичної насіннєвої продуктивності, визначено коефіцієнт насіннєвої продуктивності, виконано морфологічний опис насіння, визначено його масу та розміри. In conditions of introduction of Kyiv one of the important indicator which characterizing the biological properties of plants Darmera peltata (Torr. Ex Benth.) Voss and their level of adaptation to the new environment habitat is seed production. The learning of this issue is relevant for the development of scientific bases of generative reproduction. The results of research the features of seed productivity the plants D. peltata in natural conditions of Kyiv is given. Studied the biology of flowering plants of D. peltata on the collection plot of Botanical Garden NULES of Ukraine. Results of estimation of potential and real seed productivity are resulted, defined coefficient of seed production, results of study the morphological description of seeds, their mass and size also is given. Our results of research show the possibility of seed breeding and successful cultivation plants of D. peltata in climatic conditions in Kyiv. It will increase the range of decorative hardwood and beautifully-flowering plants to create a system of green spaces in Kyiv.
Seed Productivity of Plants Darmera peltata (Torr. еx Benth.) Voss (Saxifragaceae) in Conditions of Kiev
Keywords: Darmera peltata; real seed productivity; potential seed productivity; fruit; seeds; flower; квітка; фактична насіннєва продуктивність; потенційна насіннєва продуктивність; насіння; плід